2008
DOI: 10.3354/ame01196
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in trophic dynamics of nanoflagellates and picoplankton in coastal waters of the western subtropical Pacific Ocean

Abstract: This investigation was undertaken between August 2002 and July 2003 at a coastal station on the southern edge of the East China Sea. We found a 2-phase (warm season, > 25°C [June to October] and cold season, < 25°C [November to May]) seasonal cycle with a 10-fold variation in the growth of bacteria (heterotrophic bacteria only) and picophytoplankton, primarily coccoid cyanobacteria (Synechococcus spp.), and nanoflagellate grazing rates upon them. Growth rate in bacteria and Synechococcus spp. appeared to be af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
47
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 35 publications
9
47
1
2
Order By: Relevance
“…This may indicate a grazer saturation concentration for which grazers (if only ingesting Synechococcus) are no longer food-limited and can achieve their maximum division rates. For nanoflagellates observed in other studies, these end-bloom concentrations appear to be just slightly below ingestion saturation concentrations [20,109].…”
Section: Spring Bloommentioning
confidence: 91%
See 1 more Smart Citation
“…This may indicate a grazer saturation concentration for which grazers (if only ingesting Synechococcus) are no longer food-limited and can achieve their maximum division rates. For nanoflagellates observed in other studies, these end-bloom concentrations appear to be just slightly below ingestion saturation concentrations [20,109].…”
Section: Spring Bloommentioning
confidence: 91%
“…Strong relationships between division rate and temperature and abundance and temperature have been demonstrated for Synechococcus in temperate regions [114,1,58,60,109]. Studies investigating grazing on Synechococcus over seasonal cycles have demonstrated that heterotrophic grazers are a signification source of mortality and, depending on the season, can control Synechococcus abundances [1,109,8]. Our investigation of one annual cycle of the Synechococcus population at the Martha's Vineyard Coastal Observatory (MVCO) also found that temperature and loss rates are important.…”
Section: Introductionmentioning
confidence: 99%
“…Specific resources (inorganic nutrients) and temperature are reported to be the main limiters of growth in Synechococcus spp. (Chang et al 1996;Carlsson and Caron 2001;Tsai et al 2005), although in warmer seasons the availability of nutrients appears to be the strongest factor (Tsai et al 2008). Data from nutrient dilution experiments suggest that Synechococcus spp.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, Synechococcus spp. abundance is less than 1 × 10 4 cells mL -1 during low temperatures when there are no clear diel variations in abundance (Tsai et al 2008). Christaki et al (2002) reported that heterotrophic nanoflagellate (HNF) grazing on Synechococcus spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation